Big Data Platform for Monitoring Indoor Working Conditions and Outdoor Environment - Mishkovski, Igor; Basnarkov, Lasko; Kocarev, Ljupcho; Ilchev, Svetozar; Andreev, Rumen (My University, 2014)
This paper presents a framework and a test bed for monitoring indoor working conditions and outdoor environment. In particular, we focus on developing: i) a test bed small Wireless Sensor Network (WSN) for monitoring indoor and outdoor environment parameters using low cost Arduino controllers, transceivers and sensors, and ii) real-time platform for analysis and mining of the sensor data. Together the two integral parts will offer not only monitoring, but also mining of the data and detection of any environmental anomalies.
Keywords: Big Data, Sensor, WSN, Mining